Amyloid Beta Pathogenesis: Accelerated Amyloid Beta Pathogenesis by Bacterial Amyloid FapC (Adv. Sci. 18/2020). Issue 18 (23rd September 2020) - Javed, Ibrahim; Zhang, Zhenzhen; Adamcik, Jozef; Andrikopoulos, Nicholas; Li, Yuhuan; Otzen, Daniel E.; Lin, Sijie; Mezzenga, Raffaele; Davis, Thomas P.; Ding, Feng; Ke, Pu Chun
Abstract : In article number 2001299, Thomas P. Davis, Feng Ding, Pu Chun Ke, and co‐workers examine the aggregation of amyloid beta, the pathogenic peptide associated with Alzheimer's disease, seeded by the amyloid fragments of FapC, a protein constituent of the extracellular matrix of Pseudomonas aeruginosa that colonizes the gut microbiome through infection.